2009
DOI: 10.1007/s00198-009-0977-z
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacist-initiated screening program for osteoporosis: randomized controlled trial

Abstract: A pharmacist screening program doubled the number of patients tested for osteoporosis. Nevertheless, many patients eligible for BMD did not receive appropriate care suggesting more intensive interventions are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(129 citation statements)
references
References 35 publications
1
127
0
1
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13] In this study and previous studies, the education provided by pharmacists included an overview of osteoporosis, appropriate calcium and vitamin D intake, lifestyle measures for prevention (i.e. weight-bearing exercise, smoking cessation), and results from screenings performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8][9][10][11][12][13] In this study and previous studies, the education provided by pharmacists included an overview of osteoporosis, appropriate calcium and vitamin D intake, lifestyle measures for prevention (i.e. weight-bearing exercise, smoking cessation), and results from screenings performed.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The duration of the education sessions in this study was appropriate, based on the previous literature citing education sessions between 10 and 20 minutes. 5,6,10,13 However, the literature is absent of studies evaluating the impact of a pharmacist provided osteoporosis screening and education service on patient knowledge.…”
Section: -9;11-13mentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Several published studies have demonstrated positive health outcomes and health care cost savings as a result of community pharmacists' direct involvement with patient care. [19][20][21][22] Although several studies have compared community pharmacy and mail order with respect to cost containment and patient satisfaction, there was variation in benefit design; few have investigated patient choice of distribution channel for filling 90-day supplies of maintenance medications when benefits are equivalent. In a recently published retrospective cohort study of revealed pharmacy preference, found that when patients were given a choice between mail service and community pharmacy for 90-day supply dispensing, 44% of patients new to therapy chose community pharmacy, and 32% of those previously mandated to use mail chose community pharmacy.…”
Section: What This Study Addsmentioning
confidence: 99%
“…[13][14] These unique characteristics have the potential to provide a large population pool in community pharmacies that could be a target of preventive health services. Evidence exists in literature to support involvement of pharmacists in a broad range of activities including advice on preventive health, [15][16] diet and healthy eating [17][18] , smoking cessation, [19][20] sexual health services including emergency hormonal contraceptives, [21][22] cardiovascular risk reduction, [23][24][25] cancer prevention, 26 osteoporosis risk assessment and reduction, [27][28] and other aspects of preventive health care. [29][30] …”
Section: Introductionmentioning
confidence: 99%